Exploring the Natural Antibacterial Potential: Effectiveness of Leucaena Leucocephala Seed Extract Against Staphylococcus Aureus and Escherichia Coli - Yustika Wirda Ningsih; Asmaul Husna; Henny Umaya Fitri; Periskila Dina Kali Kulla; Rulia Meilina; Sitti Dwi Maulina (Indonesian Journal of Global Health Research, 2026)
The global rise of antibiotic resistance has encouraged researchers to investigate natural plant-based alternatives. Leucaena leucocephala (lamtoro) seeds contain bioactive compounds such as alkaloids, flavonoids, saponins, and tannins, which are suspected to possess antibacterial activity. This study aimed to assess the inhibitory effect of ethanol extract of Leucaena leucocephala seeds on the growth of Staphylococcus aureus and Escherichia coli. Method: Antibacterial activity was determined using the disc diffusion method on Mueller Hinton Agar. Extract concentrations of 5%, 10%, and 15% were tested. Aquadest served as the negative control, vancomycin (30 μg) as the positive control for S. aureus, and chloramphenicol (30 μg) as the positive control for E. coli. Each treatment was conducted in triplicate, and the inhibition zones were measured using a vernier caliper. The extract demonstrated measurable antibacterial effects on both tested bacteria. The average inhibition zones against S. aureus were 6.17 mm (5%), 6.20 mm (10%), and 6.42 mm (15%), while the positive control vancomycin showed 15.49 mm. For E. coli, inhibition zones were 6.24 mm (5%), 6.26 mm (10%), and 6.44 mm (15%), compared with 21.66 mm for chloramphenicol. The activity of the extract was classified as moderate, and higher concentrations yielded slightly larger zones. Ethanol extract of Leucaena leucocephala seeds exhibits moderate antibacterial potential against both Gram-positive and Gram-negative bacteria.